Pola Komunikasi Guru Dalam Pembinaan Akhlak Siswa di SMA Swasta Harapan Mandiri - Nugraha, Andhika (Medan Resource Center, 2022)
To ensure that youngsters have good values, moral development must be implemented. In order to realize pupils who have noble character, teachers must provide an example for their students and constantly focus on their knowledge, attitudes, and behavior as well as their worship abilities. The author conducted descriptive qualitative research for this article. The author employs observational, interview, and documentation approaches to gather data. The principal, moral aqidah instructors, and Harapan Mandiri Private High School students served as the study's main data sources. In the meantime, books about children's moral growth serve as secondary data. The collected data were then examined using data reduction analysis methods, data visualization, and conclusion-making. According to the findings of the research, it is evident that SMA Swasta Harapan Mandiri uses the proper ways to develop the morals of its pupils, including leading by example, inculcating good habits, offering guidance or understanding, and punishing or warning offenders. However, the authors of the study discovered that the lack of parental attention to their children and the students' personal development of morals at the Harapan Mandiri Private High School led to behavioral deviations on the part of the students because they lacked the necessary self-defense to keep up with the times. such that they are susceptible to peer pressure, limited parental involvement in the personality-development process, an unbalanced and economically disadvantaged upbringing, a lack of education funding, and a lack of support from the local community for an orderly educational process.